Differential Shedding and Antibody Kinetics of Zika and Chikungunya Viruses, Brazil - Bozza, Fernando A. (2019)
Fundação Oswaldo Cruz. Instituto Nacional de Doenças Infecciosas Evandro Chagas. Rio de Janeiro, RJ. Brasil.